Prevalence of Hepatitis B Virus Infection and Associated Factors Among Blood Donors in 48 Hospital Sana'a City- Yemen During 2016 - Alnwany, Naif Tawfiq (Journal of medical and pharmaceutical sciences, 2020)
Aim: This study was conducted to determine the prevalence of hepatitis B virus (HBV) and associated factors. Method: A cross-sectional study was conducted on randomly (simple random sample according to previous seroprevalence HBV in population) selected 500 blood donors from who came to the blood bank service in 48 Hospital in Sana'a between October 2016 to Aug 2016 and were interviewed face to face, then data was collected by using questionnaire and blood samples collected after that using enzyme-linked immunosorbent assay technique. the questionnaire consisted of three sections (A) demographics, (B) associated factors and (C) blood sample results. Results and conclusion: The prevalence of hepatitis B virus infected was 2.6%. Only three factors in simple and multiple logistic regression were statistically significant with prevalence of HBsAG. Multiple logistic regression analysis showed that blood donors who had history of: dental treatment, cupping and malaria infection were more likely to infect with hepatitis B virus infected compared to those without history of: dental treatment, cupping and malaria infection 7.8%, 7.3 % and 7.5 % respectively. The rest of factors failed to achieve any statistical significant with prevalence of HBsAG. Hepatitis b is hyper endemic in Yemen, this need application of infection control policies in dental clinics, cupping centers, inject Hepatitis B virus vaccine and control of malaria in endemic areas.
Keywords: hepatitis B virus; blood donors; Sana'a